PENGARUH PENERAPAN PENGAJARAN TUTOR SEBAYA DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 1 TALAMAU KABUPATEN PASAMAN BARAT - Nelvirina, Nelvirina; Zulfaneti, Zulfaneti; Yunita, Alfi (Pendidikan Matematika, 2013)
Background of the research is the understanding of mathematical concepts eighth grade students of SMP Negeri 1 Talamau still low. This is because students are embarrassed to ask and collectively with teachers and students prefer to ask friends rather than to the teacher. This study aims to determine whether students understanding of mathematical concepts using peer tutors teaching handout accompanied a better understanding of mathematical concepts than students using conventional learning in class VIII SMP Negeri 1 Talamau. This type of research is experimental research. The study population was all eighth grade students of SMP Negeri 1 Talamau listed in the school year 2013/2014. Samples were VIII1 class as the experimental class and the control class VIII3. The research instrument was a final test, the reliability is 0.887. Based on the analysis of data obtained by the average student learning outcomes experimental class was 57.71 higher than the control class is 45.10. Data analysis was obtained Â = 1.72 is greater than = 1.68. Thus, it can be concluded that the students understanding of mathematical concepts using peer tutors with teaching handouts better than students with an understanding of mathematical concepts using conventional learning in class VIII SMP Negeri 1 Talamau.